2018
DOI: 10.1016/j.neuropharm.2018.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Roflumilast promotes memory recovery and attenuates white matter injury in aged rats subjected to chronic cerebral hypoperfusion

Abstract: Chronic cerebral hypoperfusion (CCH) has been associated with aging-related vascular dementia, including Alzheimer's disease. It can be induced by the four-vessel occlusion/internal carotid artery (4VO/ICA) model in aged rats, resulting in persistent memory deficits, white matter injury, and significant neuronal loss in the hippocampus and cerebral cortex. The phosphodiesterase type 4 inhibitor (PDE4-I) roflumilast has been reported to have pro-cognitive effects in several behavioral paradigms. The present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 81 publications
5
31
0
Order By: Relevance
“…Chronic hypoperfusion is an important factor leading to vascular cognitive impairment, and it has received increasing attention in recent years. The phosphodiesterase inhibitor roflumilast [24] and the transient receptor potential melastatin 2 (TRPM2) inhibitor [25] can suppress microglial activity after CCH injury and promote cognitive function recovery through anti-inflammatory effects. IL-1β receptor inhibitors and IL-1β knockout mice block the IL-1β signaling pathway, thereby inducing oligodendrocyte premature cell migration to the periphery of the corpus callosum, and avoiding white matter damage and reversing chronic hypoperfusion-induced cognitive dysfunction by improving the local inflammatory environment [26].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hypoperfusion is an important factor leading to vascular cognitive impairment, and it has received increasing attention in recent years. The phosphodiesterase inhibitor roflumilast [24] and the transient receptor potential melastatin 2 (TRPM2) inhibitor [25] can suppress microglial activity after CCH injury and promote cognitive function recovery through anti-inflammatory effects. IL-1β receptor inhibitors and IL-1β knockout mice block the IL-1β signaling pathway, thereby inducing oligodendrocyte premature cell migration to the periphery of the corpus callosum, and avoiding white matter damage and reversing chronic hypoperfusion-induced cognitive dysfunction by improving the local inflammatory environment [26].…”
Section: Discussionmentioning
confidence: 99%
“…For Nissl staining [49], the brain slices were dewaxed with xylene and hydrated in a graded series of alcohol. Then, the samples were stained by a Nissl solution for 10 min, washed with distilled water, dehydrated by gradient alcohol, transparentized by xylene, and mounted by neutral balsam.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that CCH exacerbates neurodegeneration via multiple mechanisms, including the induction of oxidative stress which involves fatty acids, proteins, DNA, and mitochondria, blood-brain barrier disruption, increases in neuronal Ca 2+ [5], A β accumulation and aggravation [6], tau hyperphosphorylation, synaptic dysfunction, neuronal loss, white matter lesions, release of neuroinflammatory cytokines [79], excessive autophagy [10], and overactivation of microglia in the hippocampus [11, 12]. These events lead to mitochondrial dysfunction via activation of mitophagy, changes in mitochondrial morphology due to imbalance in fusion and fission events [10, 13, 14], disturbances in lipid metabolism [15], disruption of the integrity of the white matter and fiber disarrangement of the white matter [16, 17], alterations in growth factor expression [15], inhibition of neurogenesis [18], and neurotransmitter system dysfunction [2]. Furthermore, CCH can lead to the downregulation of synaptic proteins and demyelination and the reduction of dendritic spines in the hippocampus, which then leads to a reduction in synaptic transmission and neuroplasticity [12, 19, 20].…”
Section: Introductionmentioning
confidence: 99%